P108 Reclassification of aspergillosis phenotype in adult CF patients & 10 year follow up data. (December 2018) - Collier, LJ; Bright-Thomas, RJ; Denning, D; Richardson, MD; Baxter, C; Jones, AM
Abstract : Introduction and objectives: Patients from Manchester Adult Cystic Fibrosis Centre were classified for Aspergillus disease in CF (Baxter et al. 2013). These patients have been followed up for 10 years to monitor clinical outcomes and eligible patients have been re-phenotyped to investigate if their Aspergillosis phenotype has changed over time. Methods: A case note analysis was undertaken for the 129 patients, with data collected to the current day or date of death/transplant/relocation. Clinical outcomes were noted and data was gathered for age, gender, co-pathogens, antibiotic/azole treatment days, and previously identified latent class analysis of Aspergillosis. FEV1 % predicted and BMI were used to monitor clinical status. Of the original 129 patients, 79 survived to the present day without transplantation and were eligible for phenotypic reclassification using serum immunology, spontaneous sputum Aspergillus PCR, and spontaneous sputum galactomannan. Results: At 10 year follow up there was no significant difference in survival outcomes (p=0.521) between Class 1 (no disease, n=49), Class 2 (allergic bronchopulmonary aspergillosis (ABPA), n=23), Class 3 ( Aspergillus sensitised, n=19), and Class 4 ( Aspergillus bronchitis, n=38). The sole predictor of survival was FEV1 % predicted at date of consent (p<0.001). Similarly there were no significant differences in rate of decline in FEV1 (p=0.59), BMI (p=0.82) or in IV antibiotic requirements (p=0.85). Reclassification of patient's Aspergillosis phenotype is still ongoing, however there is a clearly noted rise in sputum galactomannan levels (mean=5.0) when compared to the original latent class analysis results (mean=1.33) (sputum galactomannan >0.5 is positive as per latent class analysis). Conclusions: There is no difference in mortality, clinical decline, or antibiotic therapy when comparing different phenotypes of CF Aspergillus disease. The strongest predictor of survival across all classes remains FEV1 % predicted. Sputum galactomannan appears to have increased over time. Further work is being undertaken to investigate if this affects Aspergillus disease classification. Reference: Baxter, et al . J Allergy Clin Immunol 2013September;132 (3):560–566.e10.